Effect of Chamomile capsule on premenstrual syndrome symptoms relief - Elham Najafi Mollabashi; Tahereh Ziaie; Zahra Bostani Khalesi; Ehsan Kazemnejad Leili; Reza Bekhradi (Mashhad University of Medical Sciences, 2018)
Introduction: A significant percentage of women in reproductive age experience some menstrual- related mood and physical disorders called Premenstrual syndrome (PMS). The symptoms of this syndrome can affect the various aspects of person's life. This study was performed with aim to evaluate the effect of Chamomile capsule on premenstrual syndrome symptoms relief in students. Methods: This double blind randomized clinical trial study was conducted on 118 students residing in dormitories of Guilan University of Medical Sciences in 2017 who suffered from moderate to severe premenstrual syndrome. Chamomile group received 250 mg of Chamomile powder and the subjects in placebo group received placebo 3 times a day from 7 days before menstruation until menstrual bleeding started for one cycle. Data collection tool was Premenstrual Symptoms Screening Tool (PSST). Data was analyzed by SPSS software (version 23), and independent t and paired t-test. P<0.05 was considered significant. Results: before treatment, two groups of Chamomile and placebo was not significantly different in the overall severity of premenstrual syndrome symptoms (p> 0.05). After treatment, mean score of physical, psychological and overall severity of premenstrual syndrome symptoms significantly decreased in both groups (p <0.05). However, Chamomile was more effective than placebo in relieving severity of physical, psychological and total symptoms of premenstrual syndrome (p <0. 05). Conclusion: Using of Chamomile plant effectively reduces the severity of psychological, physical and total symptoms of premenstrual syndrome.